‘Obviously, because it’s a tear it won’t necessarily mend itself’: a qualitative study of patient experiences and expectations of treatment for a meniscal tear - Charles E Hutchinson; Nicholas Parsons; Imran Ahmed; Andrew James Price; Andrew Metcalfe; Sophie Staniszewska; Chetan Khatri; Fatema G Dhaif (BMJ Open)
Objectives There is a paucity of qualitative research exploring the patient experience of living with a meniscal tear, vital to effective patient management. The aim of this study was to explore the experiences and expectations of treatment of patients aged 18–55 years with a meniscal tear of the knee.Design Qualitative study involving semistructured interviews.Setting Participants were selected from nine secondary care centres in England.Participants 10 participants diagnosed with a meniscal tear were recruited from the Meniscal Tear Outcome cohort study using a purposive sampling strategy until data saturation was achieved. Semistructured interviews were conducted between April and May 2021 and thematic analysis was used to identify key patient experiences.Results Themes identified relate to the broad areas of symptoms, clinical consultation and experience of treatment. Meniscal tears have a profound impact on pain and many patients experience effects on their family and financial life in addition to physical symptoms. Participants expected most of their management to occur in secondary care and most thought surgery would be a definitive treatment, while they believed the effectiveness of physiotherapy could not be guaranteed as it would not fix the physical tear.Conclusion This study is one of the first to explore patient experiences of a meniscal tear and their perceptions of treatment options. Patient experiences and perceptions are important for clinicians to understand in order to provide the best possible care. It is important to elicit these experiences, listen to the patient, discuss their perspectives and build these experiences and expectations into clinical care.Trial registration number ISRCTN11534691.